TESAURUS BIOTEKNOLOGI: SEBAGAI ALAT BANTU PENGINDEKSAN DOKUMEN - Tambunan, Kamariah (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2012)
Thesauri contain words or terms that are used as a tool to identify a concept or an idea precisely and correctly. The advantage of thesauri is because they are considered as better tools to find out information or document with a high degree of invention and precision. Thesauri are invaluable tools for analysts in deciding descriptors as keywords of a document. In accordance with its structure or composition, thesaurus of biotechnology consists of three parts: a hierarchy, an alphabetic, and an index. The relationships of terms from specific (narrow terms) to general (broad terms) are shown in the structure of the hierarchy. The next structure is an alphabetic, which is a form-changed from hierarchical thesaurus that is re-arranged alphabetically. The relationship between one term and other terms is shown, based on specificity level of a term meaning. The last structure is index. It is made by a team to help users browse terms in thesaurus quickly. Each of the terms will appear in alphabetical sequence with different frequencies.